2020
DOI: 10.1159/000506673
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Kidney Injury in a Patient with Renal Hypouricemia without Intense Exercise

Abstract: KeywordsExercise-induced acute kidney injury · Renal hypouricemia · Vasopressor AbstractExercise-induced acute kidney injury (EIAKI) frequently develops in patients with renal hypouricemia (RHUC). However, several cases of RHUC with acute kidney injury (AKI) but without intense exercise have been reported. We encountered a 15-year-old male with RHUC who experienced AKI. He reported no episodes of intense exercise and displayed no other representative risk factors of EIAKI, although a vasopressor had been admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…With novel Urat1 - Uox DKO mice we observed an elevation in the level of plasma Cr and BUN and a decrease of CL Cr after the forced swimming test, whereas no such fluctuation in these renal damage parameters was observed with Uox -KO mice (Figure 2, A–C). Indeed, in clinical cases it has been reported that EIAKI of RHUC1 resulted in increased serum Cr and BUN as renal damage markers 25 29 . Thus, our results suggest that novel Urat1 - Uox DKO mice induce EIAKI similar to that observed for RHUC1 patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With novel Urat1 - Uox DKO mice we observed an elevation in the level of plasma Cr and BUN and a decrease of CL Cr after the forced swimming test, whereas no such fluctuation in these renal damage parameters was observed with Uox -KO mice (Figure 2, A–C). Indeed, in clinical cases it has been reported that EIAKI of RHUC1 resulted in increased serum Cr and BUN as renal damage markers 25 29 . Thus, our results suggest that novel Urat1 - Uox DKO mice induce EIAKI similar to that observed for RHUC1 patients.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, in clinical cases it has been reported that EIAKI of RHUC1 resulted in increased serum Cr and BUN as renal damage markers. [25][26][27][28][29] Thus, our results suggest that novel Urat1-Uox DKO mice induce EIAKI similar to that observed for RHUC1 patients. In addition, Urat1-Uox DKO mice had elevated plasma UA, urinary UA/Cr ratio, and FE UA after exercise (Figure 2, D-F).…”
Section: Discussionsupporting
confidence: 81%
“…According to local availability and confidence in interpreting the results, direct genotyping with Sanger sequencing can even be considered as an early-option diagnostic tool to provide rapid genetic results and a definitive diagnosis of the disease. Of note, Sanger sequencing failed to identify pathogenic variants in three patients (8%) with a clinical picture of RHUC-AKI included in our cohort analysis [ 10 , 11 ]. In the future, MPS could be considered in order to identify additional genes involved in the pathogenesis of RHUC and to perform reliable genotype–phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…RHUC are known to be at risk for EIAKI, although RHUC may be asymptomatic except for hypouricemia [ 25 ]. It has been suggested that oxidative stress in RHUC subjects causes vasoconstriction and renal ischemia due to low blood UA, a scavenger of reactive oxygen species [ 36 ], or that high levels of UA crystallize in the renal tubules [ 11 ]. However, these hypotheses are contradictory and still controversial because EIAKI has not been reported in XU, which causes more severe hypouricemia than RHUC, and renal biopsy results of EIAKI in RHUC show few findings of UA precipitation in the renal tubular lumen or obstructive mechanisms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%